Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah (Pad)(Studi Kasus pada DPPKAD, BAPPEDA, dan BPS Kabupaten Boyolali tahun 2006-2015) - Hendriyani, Novianti; , Drs. Suyatmin Waskito Adi, M.Si (2017)
This research aimed to analyze the influence of Goverentment Ekspenditure, Population, Inflation to District Own Source Revenue ( DOSR) in Boyolali period 2006-2015. The population used in this study at Boyolali, with sample financial statement data Boyolali government in 2006-2015. The collected data were analyzed using data analysis first conducted classical assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f-tets and the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0,759 which means that 75,9% District Own Source Revenue ( DOSR) is affected Goverentment Expediture, Population, and Inflation the balance of 24,1% is influenced by other variables outside the research. Hypotesis test results showed that the Population have significant effect on District Own Source Revenue ( DOSR ), while the Goverentment Expediture and Inflation have not significant effect on District Own Source Revenue ( DOSR ).